Sobredentadura inmediata y con carga tardía: Revisión de la literatura - De Abreu, Celina Wanderley [UNESP]; Mollo Jr., Francisco de Assis [UNESP]; Chávez, Alejandro Munõz [UNESP] (My University, 2007)
The oral rehabilitation of the patients toothless totals presents large difficulties, because diverse factors act limiting the treatment with complete dentures conventional, as severe reabsorption of the alveolar process, generating for the phonetic patient difficulties and of mastication, annoyance, retention lack and stability of the prosthesis. With the emergence of you implant them osseointegratin idealized by Prof o Branemark, these aspects were improved by means of the possibility of new treatment options, as the overdentures tissue-implant-supported. However, the protocol of Branemark demanded a period of scaring from three to six months, owing the patients to await this time for the placement of the final prosthesis. This way, the surgical technique of immediate load was proposed to abbreviate this period, improving the transition phase, at the same time that it reduces the problems psychological associates. This way, the objective of the present study is to carry out a literature revision about the works that used overdentures comparing immediate and late load, the best alternative and factors wrapped in the success of the procedure discussing. © 2008 1995, Editorial Ciencias médicas.
Immediate overdenture and overdenture with late loading: Literature review
Keywords: Immediate loading; Implant; Non-loaded implant; Overdenture